Selective Interventricular Septal Radiofrequency Ablation in Patients With Hypertrophic Obstructive Cardiomyopathy: Who Can Benefit? - Liu, Qiang; Qiu, Hangyuan; Jiang, Ruhong; Tang, Xiaomei; Guo, Wenpu; Zhou, Kuangshi; Chen, Qiufan; Sun, Yaxun; Yu, Lu; Chen, Shiquan; Zhang, Pei; Sheng, Xia; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: Septal mass reduction is beneficial for hypertrophic obstructive cardiomyopathy (HOCM) patients with severe left ventricular outflow (LVOT) gradient and symptoms, with surgical myectomy or alcohol septal ablation (ASA) currently recommended in selected patients. Radiofrequency (RF) ablation of hypertrophied septum has been published as a novel method to alleviate LVOT obstruction in small populations. This study aims to investigate factors influencing clinical outcomes of radiofrequency septum ablation. Methods and results: In this study, twenty patients with HOCM who underwent endocardial ablation were included. Echocardiography and cardiac MRI (CMR) data was collected and analyzed pre- and (or) post- procedure. Nineteen patients underwent ablation successfully, while ablation was aborted in one patient with prior RBBB due to transient complete atrioventricular block (AVB). After six months of follow-up, NYHA heart functional class improved from III (2 - 3) to II (1 - 2) (p < 0.001), and resting LVOT gradient was significantly reduced (87.6 ± 29.5 mmHg vs. 48.1 ± 29.7, p < 0.001). LVOT gradient reduction was significantly higher in patients with limited basal septal hypertrophy (60.9 ± 8.3 vs. 27.9 ± 7.1, p = 0.01), shorter anterior mitral leaflet (56.1 ± 6.4 vs. 20.4 ± 5.0, p<0.01) and normally positioned papillary muscle (36.9 ± 7.1 vs. 75.0 ± 6.3, p <0.05). Conclusions: Endocardial septal ablation appears to be a safe and effective procedure for alleviating LVOT gradient in patients with HOCM, especially in those with limited basal septal hypertrophy, shorter anterior mitral leaflet and normal positioned papillary muscle.